2017
DOI: 10.1074/jbc.m117.797944
|View full text |Cite
|
Sign up to set email alerts
|

Sustained O-GlcNAcylation reprograms mitochondrial function to regulate energy metabolism

Abstract: Dysfunctional mitochondria and generation of reactive oxygen species (ROS) promote chronic diseases, which have spurred interest in the molecular mechanisms underlying these conditions. Previously, we have demonstrated that disruption of post-translational modification of proteins with β-linked -acetylglucosamine (-GlcNAcylation) via overexpression of the GlcNAc-regulating enzymesGlcNAc transferase (OGT) or GlcNAcase (OGA) impairs mitochondrial function. Here, we report that sustained alterations inGlcNAcylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 62 publications
6
95
1
Order By: Relevance
“…Zhao et al reviewed the regulatory roles of OGT in mitochondria (Zhao et al 2016). Recent findings have demonstrated that O-GlcNAcylation is widely spread among mitochondrial proteins and that mitochondrial function and oxidative stress both can be regulated by O-GlcNAcylation (Tan et al 2017). The role of OGT in placental mitochondria is under studied and warrants further investigation.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Zhao et al reviewed the regulatory roles of OGT in mitochondria (Zhao et al 2016). Recent findings have demonstrated that O-GlcNAcylation is widely spread among mitochondrial proteins and that mitochondrial function and oxidative stress both can be regulated by O-GlcNAcylation (Tan et al 2017). The role of OGT in placental mitochondria is under studied and warrants further investigation.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Our approach to measure both the open and closed sites for O-GlcNAc in theory allows us to determine this parameter for O-GlcNAcylation of a biological sample. Since O-GlcNAc regulates the energy metabolism (Tan et al, 2017) and dysregulation of O-GlcNAcylation correlates to insulin resistance in diabetes (Ma and Hart, 2013;Wollaston-Hayden et al, 2014) and tumorigenesis (Ferrer et al, 2016;Hanover et al, 2018), modification degree of O-GlcNAc could be a useful index of metabolic status and may be used for diagnosis and prognosis of cancer and diabetes.…”
Section: Figure 2 B3galnt2 Adds a Galnac Residue To O-glcnacylated Cmentioning
confidence: 99%
“…Furthermore, reducing OGT expression in liver tissue impairs mitochondrial function, and alters ROS production and antioxidant signalling (Tan et al . ). Thus it is possible that some of the sex specific effects identified in the current study may be due to the gene dosage of OGT in mouse placental tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, when OGT is deleted from the placenta, mitochondrial dysfunction occurs in the hypothalamus of offspring (Howerton & Bale, 2014). Furthermore, reducing OGT expression in liver tissue impairs mitochondrial function, and alters ROS production and antioxidant signalling (Tan et al 2017). Thus it is possible that some of the sex specific effects identified in the current study may be due to the gene dosage of OGT in mouse placental tissue.…”
Section: Effects Of Corticosterone On Mitochondrial Functionmentioning
confidence: 88%